Research areas and emerging challenges in small and medium tourism enterprises - Del Chiappa, Giacomo; Fotiadis, Anestis (Piccola Impresa / Small Business, 2019)
Tourism, with its related subsectors, is a highly fragmented sector with most tourism organizations being SMEs. Small Tourism Businesses are the backbone of the economy of many countries around the world, and Italy is certainly not an exception. Considering their varied activities, specialized services, and integration in the society, SMEs are certainly the economic lifeblood of the tourism sector, especially in developing countries, rural and remote/unprivileged areas. The aforementioned considerations contribute to explain why SMEs literature have been attracting huge attention from academics working in several disciplines such as business and management, marketing, sociology, anthropology and politics. Despite this, the engagement by academicians in research relating to SMEs in tourism can be still considered to be limited. Many research areas still need to be further investigated and deepened. This special issue was launched to call for research papers aiming to deepen our understanding about the emerging challenges in Small and Medium Tourism Enterprises.